Profiles in mental health courage - Kennedy, Patrick J. (Patrick Joseph), 1967-; Fried, Stephen, 1958- (Dutton, an imprint of Penguin Random House LLC, 2024)
"Portrays those who have struggled with their mental health. This book offers deeply compelling stories about the bravery and resilience of those living with a variety of mental illnesses and addictions"--